Utilization of workface planning for the execution of maintenance activities, shutdowns and turnarounds in petrochemical facilities – a case study. Issue 11 (2nd November 2021) - AlHamouri, Khaled; Caldas, Carlos H.; Hwang, Bon-Gang; Krishnankutty, Pramesh; de Oliveira, Daniel P.
Abstract: Maintenance activities, shutdowns and turnarounds (MST) are essential for the process industry. In fact, MST projects play important roles in maintaining the consistency of plants' productive capacity thus helping sustain corporate performance. Unfortunately, MST projects often incur significant budget and schedule overruns. This study documents the current state of practice of execution planning for MST projects. It identifies several factors that contribute to MST performance being poor. These factors include inefficiencies in execution planning, communication, scope management, measurement and control and execution safety. Utilizing input from subject matter experts (SMEs), the first part of this study focuses on developing a customized version of Workface Planning (WFP) that would be applicable to MSTs in the petrochemical industry. Once customized, the WFP tools were implemented by several petrochemical facilities. By observing this implementation, the research team was able to assess the existing levels of MST execution planning and management and to discover areas of inefficiency. This study offers ways to optimize the planning practices of executing MST. Petrochemical organizations could use these findings to assess their own current MST execution-planning procedures. This would involve implementing the customized WFP concepts and tools and thereby attain an optimal state of readiness before starting the MST execution phase.